2007
DOI: 10.1063/1.2809437
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and extremely long-lived organic light-emitting diodes based on dinaphthylperylene

Abstract: We describe a synergistic effect of a lifetime-extending light-emitting-layer (LEL) additive and improved electron injection and transport in organic light-emitting diodes (OLEDs). Previously reported di(2-naphthyl)perylene (DNP) serves as the LEL additive capable of extending the operating lifetime of OLEDs by over two orders of magnitude. Using 2-phenyl-9,10-di(2-naphthyl)anthracene (PADN) as an electron-transport layer (ETL) and a separate layer of 4,7-diphenyl-1,10-phenanthroline (BPhen) as an electron-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…67,68 Detailed mechanistic studies have shown twisted or freely rotating bonds to disassociate under irradiation and operation. 67,69,70 Lifetimes are improved by a factor of 4-200 in OLED devices that incorporate stiff molecules that strongly aggregate, 71,72 even when the chemical degradation mechanism does not involve oxygen. Generally, OLED lifetimes have improved enough to enter the commercial market, and a review of some of the latest OLED materials shows a trend of more planar, stiffer molecules.…”
Section: Photochemical Reactions In the Absence Of Oxygen And Watermentioning
confidence: 99%
“…67,68 Detailed mechanistic studies have shown twisted or freely rotating bonds to disassociate under irradiation and operation. 67,69,70 Lifetimes are improved by a factor of 4-200 in OLED devices that incorporate stiff molecules that strongly aggregate, 71,72 even when the chemical degradation mechanism does not involve oxygen. Generally, OLED lifetimes have improved enough to enter the commercial market, and a review of some of the latest OLED materials shows a trend of more planar, stiffer molecules.…”
Section: Photochemical Reactions In the Absence Of Oxygen And Watermentioning
confidence: 99%
“…A much stronger electric field is required to inject holes into NPB from ITO|CF x |CuPc than from ITO|CF x [10], as illustrated by comparing the drive voltages of otherwise identical device pairs (A,B), (C,E), and (D,F). A much smaller electric field is required to inject and transport electrons through BH|Bphen than through Alq [11], as illustrated by comparing the drive voltages of otherwise identical device pairs (C,D) and (E,F). For devices with the high-field ETL (D,F), increasing the field strength in the HTL occasions more than a doubling of the EQE.…”
Section: Resultsmentioning
confidence: 99%
“…Finally this poor interaction induced the dark spots and limited the device lifetime. [86][87][88][89][90][91] A bend test of a multilayer barrier that encapsulated a fl exible OLED display has been carried out by Chwang et al 92 The display was bent under a tensile stress 1000 times around a cylinder of one inch diameter at a rate of approximately 12 bends/min. They reported that after 100 bends the display illustrated no damage.…”
Section: Failure Mechanismsmentioning
confidence: 99%